2020
DOI: 10.1038/s41375-019-0697-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical mutatome of core binding factor leukemia

Abstract: The fusion genes CBFB/MYH11 and RUNX1/RUNX1T1 block differentiation through disruption of the core binding factor (CBF) complex and are found in 10-15% of adult de novo acute myeloid leukemia (AML) cases. This AML subtype is associated with a favorable prognosis; however, nearly half of CBF-rearranged patients cannot be cured with chemotherapy. This divergent outcome might be due to additional mutations, whose spectrum and prognostic relevance remains hardly defined. Here, we identify nonsilent mutations, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 41 publications
2
56
1
1
Order By: Relevance
“…Previous studies have shown that some of them were associated with AML. CBFB forms fusion genes CBFB/MYH11, which block differentiation in AML [24], but the deletion of CBFB usually was accompanied with the deletion of MYH11, and the deletion of MYH11/CBFB had no negative effect on the prognosis [25]. Our ndings suggested deletion-induced downregulating CBFB expression has positive effects on the prognosis.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have shown that some of them were associated with AML. CBFB forms fusion genes CBFB/MYH11, which block differentiation in AML [24], but the deletion of CBFB usually was accompanied with the deletion of MYH11, and the deletion of MYH11/CBFB had no negative effect on the prognosis [25]. Our ndings suggested deletion-induced downregulating CBFB expression has positive effects on the prognosis.…”
Section: Discussionmentioning
confidence: 60%
“…The most puzzling fact about ZBTB7A mutations in AML is their exclusive presence in the context of core binding factor leukemia, mainly in t(8;21) AML [1][2][3][4][5][6], which suggests a specific collaboration between RUNX1-RUNX1T1 and loss of ZBTB7A function. Of note, it was previously reported that RUNX1-RUNX1T1 causes a block of the monocytic and erythrocytic linages in favor of granulocytic differentiation in mouse and zebrafish [9,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others found the transcription factor ZBTB7A mutated in acute myeloid leukemia (AML) with translocation t (8;21), at frequencies ranging from 9.4 to 23% [1][2][3][4][5][6]. Hotspot mutations result either in loss (A175fs) or alteration (R402) of the C-terminal zinc finger domain, which is critical for DNA-binding of ZBTB7A [1].…”
Section: Introductionmentioning
confidence: 99%
“…Acute promyelocytic leukemia HERC1-PML genomic fusion [9] Acute Myeloid Leukemia HERC1 mutations [10] Acute lymphoblastic leukemia Decreased MSH2 protein levels and HERC1 deletions [11] Adult T-cell acute lymphoblastic leukemia HERC1 mutations [12] T-cell prolymphocytic leukemia HERC1 mutations [13] Non-melanoma skin cancer Enhanced BAK protein degradation [14] Pulmonary sclerosing pneumocytoma HERC1 mutations [15] Invasive lobular breast cancer HERC1 mutations [16] Metastatic triple-negative breast cancer HERC1 mutations [17] Sporadic colorectal cancer Decreased MSH2 protein levels and HERC1 deletions [11] Osteosarcoma Negative correlation of SOX18 overexpression and HERC1 mRNA levels [18]…”
Section: Herc1mentioning
confidence: 99%
“…Negative correlation of CCL20 overexpression and HERC5 mRNA levels [46] Reduced p53, p21 and Bax/Bcl-2 pathway activation [47] Ovarian cancer HERC5 upregulation is associated with drug resistance [48,49] Osteosarcoma Negative correlation of SOX18 overexpression and HERC5 mRNA levels [18] HERC6 Osteosarcoma Negative correlation of SOX18 overexpression and HERC6 mRNA levels [18] Mutations in large HERCs have been found in leukemia [10][11][12][13] and breast cancer [16,17]. Frameshift mutations in HERC2 have been found in both gastric and colorectal carcinomas with microsatellite instability [31].…”
Section: Herc2mentioning
confidence: 99%